North American MNCs and their HR policies in liberal and co-ordinated market economies - Parry, Emma; Dickmann, Michael; Morley, Michael (Taylor & Francis, 2008)
We explore the landscape of HRM in North American MNCs which have been for long characterized as having an express preference for institutionalizing aspects of the home business system when operating aboard. Drawing upon institutional theory, both the USA and Canada are identified as liberal market economies. Building on this, we examine the HR preferences of subsidiaries originating in North America and operating in diverse liberal and coordinated market economies in order to test the extent to which the host context influences the pattern of HR policies and practices pursued, referring predominantly to the literature on USA firms. The results indicate that the pattern of HR practices pursued by North American owned MNCs varies widely depending on whether these North American owned MNCs are operating in liberal or coordinated market economies, lending support to the importance of context as a determinant of the likelihood of, and limits to, the transfer of HRM practices and preferences.
Keywords: Localization of HR practices; Multi-national corporations; Varieties of capitalism